How to keep well in wartime - Great Britain. Ministry of Health ; Central Council for Health Education (Great Britain); Clegg, Hugh Anthony, 1900- (London : His Majesty's Stationery Office, 1943)
1943 1943 1940s 28 pages : illustrations KEEP MIND AND BODY ACTIVE if the war makes it advisable for you to spend your holiday at home. Make the Most of Spare Time. It is just as necessary to relax, mentally and physically, during the ordinary working week. The best way of doing this will vary according to circumstances. If your work is of the hard manual kind your muscles will be tired and what you need most perhaps is actual rest. If your job keeps you standing all day or if it involves monotonous repetition, you probably need a change, such as walking, more than rest. (Girls and women should wear low heels for standing and walking.) If you sit all day in an office or a workshop you won't be physically or muscularly tired but you may feel jaded and too tired to take exercise. What is needed, whatever your work, is change of activity, something that will exercise those of your muscles that you haven't been using during the day, and won't be using on your Home Guard parade or in your Civil Defence duties. For most of us exercise is essential if health is to have a polish on it. If possible some form of exercise should be taken daily in the open air. One way of doing this is to get up half an hour earlier in the morning, and walk part of the way to work. If you are not too tired at the end of the day you might also walk part of the way back. During this war many people have begun to cycle to work and have felt better for it. Muscles are Meant to be Used. Those masses of muscle on arm, leg, thigh, back, and belly are not just ornamental. They are there to be used. If they are not used they will sooner or later let you know about it. Muscular rheumatism is a common complaint in this country, and one precaution to take against it is to keep joints and muscles on the go so that the blood flows freely through them. Are your muscles becoming set ? Can you, standing with knees straight, touch the tips of your toes with the tips of your fingers ? Try it. In your weekends, when you can, walk, cycle, swim, dig, row a boat, and enjoy it. Don't put it off. Start now, and never mind feeling stiff to begin with. Advice to the Fat. If you are overweight you must start your exercise gradually, and increase it gradually. It is true that some people are fat by nature. In others fatness may be the result of disease. In many people fatness is the result of a combination of over-eating and lack of exercise. A man called Daniel Lambert created what must be a record of fatness. He weighed 52 stone and his waist measurement was 9 feet 4 inches. He died before he was forty. Insurance companies say that fat men do not live so long as thin men. If you are overweight and feel that your health is not up to scratch, seek your doctor's advice before you do anything about it. Whatever 7 420/BS/7/16/18